PERTIMBANGAN HUKUM HAKIM (RATIO DECIDENDI) TERHADAP PENJATUHAN PIDANA ANAK PELAKU PENCABULAN - Nasrul Alief Pratama; Bambang Santoso (Sebelas Maret University, 2023)
This article aims to determine the provisions of criminal acts of children as perpetrators of sexual harrasment based on Law Number 11 of 2012 concerning the Child Criminal Justice System in the study of decision Number 16/Pid.Sus-Anak/2020/PN Wng. The method used in this research is perspective and applied normative legal research, namely research using primary legal materials and secondary legal materials. The approach used by the author in this research is a case approach. Based on the results of the author's research, the Judge's consideration in imposing punishment on children in the process of obscenity cases in Decision Number 16/Pid.Sus-Anak/2020/PN Wng is in accordance with Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection and Law No. 11 of 2012 concerning the Child Criminal Justice System, namely in the form of imprisonment for 8 (eight) months and work training for 3 (three) months at Wonogiri Detention Center. Diversion cannot be applied in the crime of sexual harrasment with child perpetrators in accordance with Article 7 paragraph (2) of the SPPA Law which states that diversion can be applied to children who commit criminal offenses with a criminal penalty of under 7 (seven) years and not repetition of criminal acts. Keywords: Child; Child Sexual Harassment; Judge's Consideration